MC Kinsey 7S Frame Work Approach Method to the Effectiveness of Organizational Performance in the Directorate of Preschool Teachers and Community Education Ministry of Education, Culture, Research and Technology - Oktafiany, Andini; Rivai Zainal, Veithzal; Hakim, Azis (Journal of Economics and Business UBS, 2023)
Organizational effectiveness is the level of accuracy or success of an organization in formulating clear goals, realizing household budgets, managing individual activities in the organization in the form of standard operational procedures, obtaining organizational members who are in accordance with their roles, duties, functions and activities. to achieve organizational goals. The aim of this research is to find out: a) a description of the organizational effectiveness of the Directorate of Early Childhood and Community Education Teachers. b) influencing factors and efforts made to increase effectiveness in the Directorate of Early Childhood and Community Education. The research method uses a qualitative descriptive case study design. Qualitative research is defined as a type of research whose findings are not obtained through statistical procedures or other forms of calculation. Based on the results of the research that has been carried out, it can be concluded that: 1) From the results of the research, the picture of organizational effectiveness in the Directorate of Early Childhood Teachers and Community Education is that each section has carried out its duties and functions as expected. job descriptions, so that organizational goals can be achieved well. 2) Factors that influence the effectiveness of organizational performance in the Directorate of Early Childhood Teachers and Community Education include human resources; Leadership and Employee Competencies. 3) Efforts made to increase the effectiveness of organizational performance at the Directorate of Early Childhood Teachers and Community Education are Empowerment; Teamwork, Developing Abilities, and Motivation.